Balance of Theory and Practice Teaching Materials in Increasing Female Students' Motivation and Interest in Participating in Dance Extracurriculars - Nia Rahmadani; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study was to determine the learning interest of students in the class of SMK Negeri 5 Padang and the factors that influence student interest in dance at SMK Negeri 5 Padang. This type of research is qualitative research with a descriptive approach. This research instrument: is the researcher himself and is assisted by supporting equipment such as stationery, mobile phones and recorders. Data collection techniques through literature study, observation, interviews and documentation the stages of exploratory analysis are data collection, data reduction, data presentation and conclusions. The lack of student interest in learning outside Dance in the material of the cultural arts teacher of SMK Negeri 5 Padang did not update the teaching material and also did not change the teaching method. Factors that influence student interest in non-dance education at SMK Negeri 5 Padang are internal and external factors.